Risk factors for methicillin-resistant Staphylococcus aureus colonization in a level-IV neonatal intensive care unit: a retrospective study - Julia Elzbieta Galuszka; Kim Thomsen; Jenny Dahl Knudsen; Rikke Louise Stenkjaer; Rikke Nielsen; Karen Leth Nielsen; Andreas Petersen; Barbara Juliane Holzknecht; Mette Damkjaer Bartels; Morten Breindahl; Lise Aunsholt (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract